Prosedur Pengambilan Data Kepulangan Pekerja Migran Indonesia oleh UPT P2TK di Bandara Internasional Juanda Surabaya - Azarine Auranayya Selaksa Fitri; Oktarizka Reviandani (IAI Nasional Laa Roiba Bogor, 2026)
The increase in Indonesia’s population without adequate job availability has driven many citizens to work abroad as Indonesian migrant workers (PMI). While labor migration contributes to foreign exchange and individual welfare, it also poses significant risks, particularly for non-procedural PMI who are vulnerable to rights violations, exploitation, and human trafficking. Consequently, the state is obligated to ensure comprehensive protection, including during the repatriation process. This study aims to describe the procedures for collecting repatriation data of PMI by the Technical Implementation Unit for Labor Services and Protection (UPT P2TK) at Juanda International Airport, identify existing obstacles, and assess the implementation of government service and protection functions. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews with UPT P2TK officers, and documentation review. The findings indicate that data collection is conducted through arrival monitoring, document verification, brief interviews, and daily data compilation using an online system, reflecting government functions of service, development, and protection. However, low reporting awareness among PMI and limited personnel amid fluctuating arrivals hinder data accuracy, highlighting the need for improved socialization and strengthened human resources to optimize post-employment protection.